2022
DOI: 10.1177/23259671211073905
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Factors Associated With an Increased Incidence of Intra-articular Injuries After Delayed Anterior Cruciate Ligament Reconstruction

Abstract: Background: Delays from the time of an anterior cruciate ligament (ACL) tear to surgical reconstruction are associated with an increased incidence of meniscal and chondral injuries. Purpose: To evaluate the association between delays in ACL reconstruction (ACLR) and risk factors for intra-articular injuries across 8 patient demographic subsets. Study Design: Cross-sectional study; Level of evidence, 3. Methods: We performed a retrospective chart review of all patients who underwent ACLR from January 2009 to Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Nevertheless, the impact of timing of surgery on meniscus damage in the isolated ACL reconstruction is well known in the literature. Many studies report a higher risk of overall meniscus tear, especially of the medial meniscus in delayed surgery compared to early surgery [6,8,10,[43][44][45][46]. The literature has widely demonstrated in long-term the superiority of meniscus repair in terms of function, return to sports and also cartilage protection, even more since high-energy knee injury increase the long-term risk of post-traumatic osteoarthritis [27,35,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the impact of timing of surgery on meniscus damage in the isolated ACL reconstruction is well known in the literature. Many studies report a higher risk of overall meniscus tear, especially of the medial meniscus in delayed surgery compared to early surgery [6,8,10,[43][44][45][46]. The literature has widely demonstrated in long-term the superiority of meniscus repair in terms of function, return to sports and also cartilage protection, even more since high-energy knee injury increase the long-term risk of post-traumatic osteoarthritis [27,35,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Among adults, we did not detect greater risk of new medial or lateral meniscal tears after delayed ACL reconstruction, despite the larger sample size. Stone et al 39 similarly reported that ACL reconstruction between 90 days and 1 year after injury in adults aged 40 years was not || References 3,12,15,[17][18][19]21,24,26,27,28,29,32,34,39,43.…”
Section: Discussionmentioning
confidence: 99%